Vasoactive effect of fibronectin‐derived epiviosamine‐1 and related peptides in quiescent and stress models. (August 2017) - Frame, Mary D.; Lin, Fubao; Dewar, Anthony M.; Clark, Richard A. F.
Abstract: Objective: Following thermal burn injury, plasma fibronectin degrades within the interstitium; one possible product is EVA‐1, PSHISKYILRWRPK found within the FNIII1 . EVA‐1 ameliorates thermal burn injury progression, and binds to and enhances PDGF‐BB in promoting cell metabolism, growth and survival; shorter related peptides lose these abilities. Here we study the effect of EVA‐1 and shorter peptides for their vasoactivity under quiescent and stress conditions. Methods: Using the hamster cheek pouch intravital microscopy model, five EVA‐1 related peptides were applied to small arterioles via micropipette (10 −16 ‐10 −4 mol L −1 ) in quiescent tissue and after defined stress: nitric oxide or heat. Results: Peak dilation occurred with nanomolar doses (longer peptides) or below (shorter peptides), blocked by propranolol (beta‐adrenergic receptor antagonist). Micromolar doses of the same peptides induced only constriction, not antagonized by phentolamine (alpha‐adrenergic receptor antagonist). Scrambled variants of two peptides yielded only constriction, suggesting constriction might be due peptide charge. Each stressor caused a left shift in dilation response, blocked by carazolol. Conclusions: Thus, this important region of FNIII1 contains sequences that have a gradation of biological functions dependent on the length of the peptide sequence, with increased efficacy for dilation following stressors.